Maintenance in the construction industry - Knezevic, Jezdimir, 1953- (Journal of quality in maintenance engineering ;, 2002)
About the Guest Editor Jezdimir Knezevic is the President of the MIRCE Akademy of SystemOperational Science and professor at its School for System Operational Solutions. His 20 years ofacademic and professional experience in reliability, maintenance and logistics engineering, hasbeen summarised through over 200 technical and scientific publications. He has also authoredseveral books, including Reliability, Maintainability and Supportability - A ProbabilisticApproach and Systems Maintainability. He has received international awards for hiscontribution to the file of logistics engineering and ed.